QUALIFICATION MISMATCH DAN UPAH DI INDONESIA - Heny Wulandari; Arie Damayanti (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2021)
Abstract Qualification mismatch is one of the biggest problems in the labor market in the past few years. Based on the previous researchs, qualification mismatch has serious effects on labor outcomes such as wages. Therefore, this study aims to estimate the incidence of qualification mismatch and its relationship with wages in Indonesia. This study uses individual Sakernas data set from 2017 to 2018. Empirical results show that the incidence of undereducation is higher than overeducation. Moreover, the estimation results using fixed effect (FE) method show that overeducation and undereducation has no significant effect on wages. Wages are only affected by the level of education required, while the excess and shortage years are not taken into account. This findings calls for the policies intended to resolve the problem of qualification mismatch.